Candidose experimental e recuperação de candida albicans na cavidade bucal de ratas ovariectomizadas - Junqueira, Juliana Campos [UNESP] (2003)
The purpose of this work was to observe the development of candidosis and the recovery of C. albicans from the oral cavity of control and ovariectomized rats. Hundred twenty-four rats originally negative for the Candida spp. in the oral cavity were divided into two groups: control and ovariectomized. ln each group, four rats were used for tongue dorsum morphologic analysis by optical microscope and scanning electron microscope; and 58 rats received inoculations of C. albicans for the study of candidasis and recovery of yeasts. The development of candidosis on the tongue dorsum was observed in optical microscope and scanning electron microscope in the periods of six hours, 24 hours, seven days and 15 days after the last inoculation. The recovery of C. albicans was performed through oral samples collected at one, two, tive, seven days and progressively at each 15 days until negative cultures for the yeasts were obtained. The results were statistically analyzed by the t-student and Mann-Whitney tests. The tongue dorsum of the control and ovariectomized rats, not infected by Candida, presented normal aspect. Among lhe infected rats, the ovariectomized group showed less quantity of candidosis lesions in relation to control. The recovery of C. albicans from the oral cavity of ovariectomized animals was lower in relation to control in all periods of observation. lt could be concluded lhat candidosis and recovery of C. albicans ln the oral cavity of rats were less frequent in the ovariectomized group in relation to control